The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/bdcc7020093
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence for Fraudulent Banking Operations Recognition

Bohdan Mytnyk,
Oleksandr Tkachyk,
Nataliya Shakhovska
et al.

Abstract: This study considers the task of applying artificial intelligence to recognize bank fraud. In recent years, due to the COVID-19 pandemic, bank fraud has become even more common due to the massive transition of many operations to online platforms and the creation of many charitable funds that criminals can use to deceive users. The present work focuses on machine learning algorithms as a tool well suited for analyzing and recognizing online banking transactions. The study’s scientific novelty is the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The findings revealed that ANN performed well, with an F1 score of 0.91. Regarding banking transaction fraud detection context, Mytnyk et al [14] have compared seven machine learning models: RF, k-nearest neighbors (KNN), LR, stochastic gradient descent (SGD), decision tree (DT), naive Bayes (NB), and SVM on a transactional dataset. According to the findings of the various methods, the LR works better, yielding a final AUC value of around 94.6%.…”
Section: Online Banking Fraud Detection Tacticsmentioning
confidence: 99%
“…The findings revealed that ANN performed well, with an F1 score of 0.91. Regarding banking transaction fraud detection context, Mytnyk et al [14] have compared seven machine learning models: RF, k-nearest neighbors (KNN), LR, stochastic gradient descent (SGD), decision tree (DT), naive Bayes (NB), and SVM on a transactional dataset. According to the findings of the various methods, the LR works better, yielding a final AUC value of around 94.6%.…”
Section: Online Banking Fraud Detection Tacticsmentioning
confidence: 99%
“…The authors in [2] underscore the significance of leveraging artificial intelligence for the detection of fraudulent banking transactions. They introduce several classification algorithms applied to discern transaction types based on specific features.…”
Section: Accepted Papers Overviewmentioning
confidence: 99%
“…In addition to detecting fraud and fraud in organizations, fraud detection techniques and intelligence tools aim to predict future behavior and reduce the risk of fraud by understanding user and customer behavior. Banks and financial institutions are striving to speed up the process of identifying fraudsters due to the high costs of fraud (1)(2)(3). It is against the law to commit fraud in electronic banking and electronic money transfer.…”
Section: Introductionmentioning
confidence: 99%